Perancangan Buku Ilustrasi Tradisi Tiyu sebagai Media Informasi Bagi Siswa SMKN 3 Selong - Nurhaliza Rahmayani; Hasbullah Hasbullah; I Gede Anjas Kharisma Nata (Journal of Innovative and Creativity (Joecy), 2026)
The Tiyu Tradition is a horse-riding activity carried out by the community of Jantuk Village, Sukamulia District, East Lombok Regency, on every Eid al-Fitr celebration, and holds a close connection to the history and ancestral identity of the local community. A survey of 60 respondents outside Jantuk Village revealed that only 58.3% were aware of this tradition, while 41.7% were not, indicating that the dissemination of information about this tradition to the wider public remains limited. This study aims to design an illustrated book on the Tiyu Tradition as a communicative and easily understandable cultural information medium to support the introduction and preservation of local culture. This study employs a qualitative method with a Design Thinking approach, consisting of five stages: Empathize, Define, Ideate, Prototype, and Test. Data were collected through observation, interviews, documentation, questionnaires, and literature study. The design outcome is an illustrated book on the Tiyu Tradition as an informative visual medium, serving as an alternative media to support the introduction and preservation of local culture.